A cerato-platanin protein SsCP1 targets plant PR1 and contributes to virulence of Sclerotinia sclerotiorum - Yang, Guogen; Tang, Liguang; Gong, Yingdi; Xie, Jiatao; Fu, Yanping; Jiang, Daohong; Li, Guoqing; Collinge, David B.; Chen, Weidong; Cheng, Jiasen (The New phytologist, 2018)
Cerato-platanin proteins (CPs), which are secreted by filamentous fungi, are phytotoxic to host plants, but their functions have not been well defined to date. Here we characterized a CP (SsCP1) from the necrotrophic phytopathogen Sclerotinia sclerotiorum. Sscp1 transcripts accumulated during plant infection, and deletion of Sscp1 significantly reduced virulence. SsCP1 could induce significant cell death when expressed in Nicotiana benthamiana. Using yeast two-hybrid, GST pull-down, co-immunoprecipitation and bimolecular florescence complementation, we found that SsCP1 interacts with PR1 in the apoplast to facilitate infection by S. sclerotiorum. Overexpressing PR1 enhanced resistance to the wild-type strain, but not to the Sscp1 knockout strain of S. sclerotiorum. Sscp1-expressing transgenic plants showed increased concentrations of salicylic acid (SA) and higher levels of resistance to several plant pathogens (namely Botrytis cinerea, Alternaria brassicicola and Golovinomyces orontii). Our results suggest that SsCP1 is important for virulence of S. sclerotiorum and that it can be recognized by plants to trigger plant defense responses. Our results also suggest that the SA signaling pathway is involved in CP-mediated plant defense.